Impact of Age and Baseline NIHSS Scores on Clinical Outcomes in the Mechanical Thrombectomy Using Solitaire FR in Acute Ischemic Stroke Study - Almekhlafi, M.A.; Davalos, A.; Bonafe, A.; Chapot, R.; Gralla, J.; Pereira, V.M.; Goyal, M. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: Age and stroke severity are inversely correlated with the odds of favorable outcome after ischemic stroke. A previously proposed score for Stroke Prognostication Using Age and NIHSS Stroke Scale (SPAN) indicated that SPAN-100-positive patients (ie, age + NIHSS score = 100 or more) do not benefit from IV-tPA. If this finding holds true for endovascular therapy, this score can impact patient selection for such interventions. This study investigated whether a score combining age and NIHSS score can improve patients' selection for endovascular stroke therapy. MATERIALS AND METHODS: The SPAN index was calculated for patients in the prospective Solitaire FR Thrombectomy for Acute Revascularization study: an international single-arm multicenter cohort for anterior circulation stroke treatment by using the Solitaire FR. The proportion with favorable outcome (90-day mRS score ≤2) was compared between SPAN-100-positive versus-negative patients. RESULTS: Of the 202 patients enrolled, 196 had baseline NIHSS scores. Fifteen (7.7%) patients were SPAN-100-positive. There was no difference in the rate of successful reperfusion (Thrombolysis In Cerebral Infarction 2b or 3) between SPAN-100-positive versus -negative groups (93.3% versus 82.8%, respectively; P = .3). Stroke SPAN-100-positive patients had a significantly lower proportion of favorable clinical outcomes (26.7% versus 60.8% in SPAN-100-negative, P = .01). In a multivariable analysis, SPAN-100-positive status was associated with lower odds of favorable outcome (OR, 0.3; 95% CI, 0.1–0.9; P = .04). A higher baseline Alberta Stroke Program Early CT Score and a short onset to revascularization time also predicted favorable outcome in the multivariable analysis. CONCLUSIONS: A significantly lower proportion of patients with a positive SPAN-100 achieved favorable outcome in this cohort. SPAN-100 was an independent predictor of favorable outcome after adjusting for time to treatment and the extent of preintervention tissue damage according to the Alberta Stroke Program Early CT Score. SPANStroke Prognostication Using Age and NIH Stroke ScaleSTARSolitaire FR Thrombectomy for Acute Revascularization study